Counseling On The Benefits Of Air Circulation In The House As An Effort To Prevent TB Disease - Akas Yekti Pulih Asih; Budhi Setianto; Agus Aan Adriansyah; Effendi; Yauwan Tobing Lukiyono; Nathalya Dwi Kartika Sari; Nikmatus Sa’adah (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT, 2024)
One way to prevent TB is to maintain air circulation in the house. Good air circulation in the house is essential to create a healthy and comfortable environment. Good air circulation ensures fresh air. Community service aims to help provide insight to the community regarding the benefits of healthy air circulation at home as an effort to prevent TB disease in the work area of the Wonokromo sub-district health centre, Surabaya City. The service method used is counselling about tuberculosis with partners who are 62 residents of RW 05, Wonokromo Village, Surabaya City. The results of the community service can be concluded that the extension of the benefits of indoor air circulation as an effort to prevent TB disease can increase public knowledge about pulmonary tuberculosis in the work area of RW 07, Wonokromo Village. The results of implementing community service can significantly increase community knowledge about pulmonary tuberculosis by 86.6%. Suggestions: Regular education needs to be carried out as an effort to eliminate TB so that the morbidity rate for pulmonary tuberculosis in Wonokromo Village decreases.